The metabolic syndrome in mice overexpressing neuropeptide Y in noradrenergic neurons. Issue 1 (July 2017) - Ailanen, Liisa; Ruohonen, Suvi T; Vähätalo, Laura H; Tuomainen, Katja; Eerola, Kim; Salomäki-Myftari, Henriikka; Röyttä, Matias; Laiho, Asta; Ahotupa, Markku; Gylling, Helena; Savontaus, Eriika
Abstract : A gain-of-function polymorphism in human neuropeptide Y ( NPY ) gene (rs16139) associates with metabolic disorders and earlier onset of type 2 diabetes (T2D). Similarly, mice overexpressing NPY in noradrenergic neurons (OE-NPY DBH ) display obesity and impaired glucose metabolism. In this study, the metabolic syndrome-like phenotype was characterized and mechanisms of impaired hepatic fatty acid, cholesterol and glucose metabolism in pre-obese (2-month-old) and obese (4–7-month-old) OE-NPY DBH mice were elucidated. Susceptibility to T2D was assessed by subjecting mice to high caloric diet combined with low-dose streptozotocin. Contribution of hepatic Y1-receptor to the phenotype was studied using chronic treatment with an Y1-receptor antagonist, BIBO3304. Obese OE-NPY DBH mice displayed hepatosteatosis and hypercholesterolemia preceded by decreased fatty acid oxidation and accelerated cholesterol synthesis. Hyperinsulinemia in early obese state inhibited pyruvate- and glucose-induced hyperglycemia, and deterioration of glucose metabolism of OE-NPY DBH mice developed with aging. Furthermore, streptozotocin induced T2D only in OE-NPY DBH mice. Hepatic inflammation was not morphologically visible, but upregulated hepatic anti-inflammatory pathways and increased 8-isoprostane combined with increased serum resistin and decreased interleukin 10 pointed to increased NPY-induced oxidative stress that may predispose OE-NPY DBH mice to insulin resistance. Chronic treatment with BIBO3304 did not improve the metabolic status of OE-NPY DBH mice. Instead, downregulation of beta-1-adrenoceptors suggests indirect actions of NPY via inhibition of sympathetic nervous system. In conclusion, changes in hepatic fatty acid, cholesterol and glucose metabolism favoring energy storage contribute to the development of NPY-induced metabolic syndrome, and the effect is likely mediated by changes in sympathetic nervous system activity.